2018
DOI: 10.1016/j.dld.2018.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Increase in chromogranin A- and serotonin-positive cells in pouch mucosa of patients with ulcerative colitis undergoing proctocolectomy

Abstract: We here demonstrated neuroendocrine cell hyperplasia in pouch mucosa. Further studies are needed to clarify the pathophysiological implication of this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…EEC are considered key players in the pathogenesis of inflammatory bowel disease (IBD) and possible therapeutic targets in these patients 5 . NEC hyperplasia has been described by various authors in patients with ulcerative colitis, Crohn's disease, microscopic colitis and irritable bowel syndrome, probably as response to inflammation [6][7][8][9][10][11][12][13][14][15] . Some authors also reported the presence of very small incidental NEC proliferations in ulcerative colitis patients 10,16 .…”
Section: Introductionmentioning
confidence: 99%
“…EEC are considered key players in the pathogenesis of inflammatory bowel disease (IBD) and possible therapeutic targets in these patients 5 . NEC hyperplasia has been described by various authors in patients with ulcerative colitis, Crohn's disease, microscopic colitis and irritable bowel syndrome, probably as response to inflammation [6][7][8][9][10][11][12][13][14][15] . Some authors also reported the presence of very small incidental NEC proliferations in ulcerative colitis patients 10,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the 5-HT system has been demonstrated to play a role in the pathophysiology of gut disorders including IBD. Interestingly, expression of mucosal SERT is decreased in experimental colitis [27,28] as well as in IBD patients [29][30][31][32]. Conversely, SERT KO mice which lack high affinity transport of 5-HT into the intracellular compartment are more susceptible to intestinal inflammation [33,34].…”
Section: Introductionmentioning
confidence: 99%